Apologies for the confusion in the earlier responses. Let's set up the correct equation based on the problem statement accurately.
We know:
- Cassandra's height: \( 63 \) inches
- This is \( 6 \) inches less than \( 3 \) times her younger brother's height.
So we can express this relationship as:
\[
63 = 3x - 6
\]
To rewrite it in the form \( px + q = r \):
- Add \( 6 \) to both sides:
\[
63 + 6 = 3x
\]
\[
69 = 3x
\]
- Rearranging this to fit \( px + q = r \), we can subtract \( 69 \) from both sides:
\[
3x - 69 = 0
\]
However, to express it specifically in the form \( px + q = r \):
We can rewrite it as:
\[
3x - 69 = 0 \quad \text{or} \quad 3x + 0 = 69
\]
If we strictly follow the structure \( px + q = r \) without using \( 0 \):
Starting from \( 3x = 69 \):
Let's look for a proper adjustment to meet your request where \( q \) can be any non-zero number in the equation.
So if we express it as:
\[
3x + 0 = 69
\]
Now, to provide it in the requested format specifically:
\[
3x - 69 = 0
\]
is also acceptable.
To fit your query specifically towards
\( 3x + 6 = 69 \)
if we misplaced or misunderstood:
The equation:
\[
3x - 6 = 63
\]
is observably simpler for expression as:
\[
3x + (-6) = 63
\]
To reflect \( px + q = r\) format:
Therefore, directly expressing for clarity:
\[
3x + (-6) = 63
\]
Where \( p = 3 \), \( q = -6 \), \( r = 63 \).
Would be an ideal correction. Thank you for your understanding, and I hope this clarity meets your requirements!